Analisis Ketermpilan Proses Sains dan Hasil Belajar Siswa Kelas V Menggunakan Model Problem Based Learning pada Materi Energi dan Perubahannya di SD Negeri Seuneubok Johan - Daulai, Nurmayani; Sari, Siti Mayang; Akmaluddin, Akmaluddin (Indo-MathEdu Intellectuals Journal, 2023)
Process science skills are an important part of the Natural and Social Sciences, as process science skills can help students understand the world around them, think critically and creatively and can apply their knowledge to solve problems. To achieve science process skills, a learning model is needed that can encourage students to associate material with phenomena This study aims to determine the science process skills and learning outcomes of grade V students by using the PBL learning model on energy materials and their changes at SDN Seuneubok Johan East Aceh. The sample in this study was grade V students totaling 32 students. Data collection techniques use test techniques and observation sheets. The research data were analyzed using descriptive analysis. The results of the analysis and science process skills and student learning outcomes obtained showed that the average percentage of the eight indicators of science process skills and the four types of assessment of learning outcomes was in the range of 61%-100% values with good (77.26%) and very good (94.15%) categories, so it can be concluded that there is an influence in the use of PBL learning models on science process skills and student learning outcomes